Impacts of Foreign Direct Investment on Economic Growth of Nepal: A Johansen Co-integration Analysis - Poudel, Omkar (Journal of Balkumari College, 2022)
This research study analysed the impacts of FDI on Nepalese economy using data over the period of 1995- 2020. The descriptive and analytical research design has been used. To quantify the effects of independent variables on the dependent variable, data are taken from secondary sources of Nepal Rastra Bank and ministry of finance were employed to measure the variables. In order to interpret the data, the acquired data were analysed by using E-views Statistical Package version 10. Augmented Dickey- Fuller Test is run to test stationary condition in the variables. As per the study, result of Johansen Co-integration Test supported the existence of co-integration in the model. The coefficient of VECM was positive and insignificant expresses that there was no evidence of long run relationship. However, there was found short run causality between GFCF and GDP. Granger Causality Test indicated the two way causality between GFCF and GDP, GFCF with FDI and one way causality from GDP to FDI. The finding shows that the overall model was statistically significant. Furthermore, the GDP was significantly associated with GFCF (p-value=0.0334). 78.53 % of the GDP as explained by the GFCF whereas there was no significantly associated with GDP on FDI.